Evaluation of plated versus grated process deck in Foating Production Storage and Offloading (FPSO) from explosion perspective using safety offshore - Porselvam, Umamaheswari; Mohamed Yusoff, Hamdan; Nik Ibrahim, Nik Nor Liyana (Universiti Putra Malaysia Press, 2020)
Vapor cloud explosion is one of the major threats to Floating, Production, Storage and Offloading (FPSO) facilities due to its congested and confined nature. Reduction in explosion overpressure can be achieved by improving the ventilation in FPSO. During early design stage of FPSO, designers consider providing grated process decks to improve the ventilation. However, there is limited research on the comparison of the explosion overpressure between the grated deck and the traditional plated deck. In this study, Vapor Cloud Explosion perspective of plated versus grated process deck in typical FPSO was evaluated by utilizing Det Norske Veritas’s (DNV) SAFETI OFFSHORE modelling tool. Representative leak scenarios were selected based on frequency analysis of major accident hazards associated with typical FPSO facility. This study revealed that the overpressure exceedance frequency in plated process deck was higher than the grated process deck for the selected scenario. This serves as quantitative guidance for designers to select an inherently safer type of decks in FPSOs from explosion perspective during the preliminary design stage. However, a detailed Computational Fluid Dynamics (CFD) study is recommended to get an insight of dangers associated with the presence of plated and grated process decks in FPSO, by considering all the parameters and conditions applicable.